Business Assignments. Information File. - Casler, Ken and Palmer, David (Oxford Oxford University Press, 1995)
Business Assignments is a set of eight international case studies with video for advanced learners of Business English. In Each case, extensive input material builds a realistic and motivating business problem, culminating in a challenging and authentic simulation, or assignment. Busisness Assignments covers numerous key areas of business language, including presentations, negotiations, management meetings, and technical briefings as well as informal socializing.
Keywords: Business English